2009
DOI: 10.1002/zoo.20213
|View full text |Cite
|
Sign up to set email alerts
|

First observations of nest attendance behavior by wild maned wolves, Chrysocyon brachyurus

Abstract: In many species of canids the male's role in reproduction extends to providing extensive or some parental care to his offspring. Maned wolves are a monogamous canid species whose males have been observed providing parental care to their offspring in captivity, but no field observations exist. We observed a wild pair of maned wolves at their nest site in a period soon after the female had given birth for a total period of 65 days. We made five observation sessions with an average of 3-4 days each separated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…dISCuSSIOn hoMe ranGe size Telemetry-generated maned wolf home range areas reported in the recent literature are in the same size range that we found for Los Fierros (Coelho et al, 2008;Jácomo et al, 2009;Melo et al, 2007;Rodrigues, 2002), suggesting similar ecological conditions. The largest such study, of 37 resident adult MW studied by Jácomo et al (2009) of our study, two MW co-occupying the same range used areas of 40 km 2 (vHF, perhaps an underestimate) and 52 km 2 : more like the smaller ranges of 20-40 km 2 reported by Dietz (1984) and 40-50 km 2 reported by Trolle et al (2007) and Melo et al (2009). In our study, increases in range sizes after 2005 corresponded to a decline in prey numbers (Emmons, 2009), which suggests an influence of resource density on range size, as we report in more detail in Chapters 4 and 5.…”
Section: Territorialitysupporting
confidence: 44%
See 4 more Smart Citations
“…dISCuSSIOn hoMe ranGe size Telemetry-generated maned wolf home range areas reported in the recent literature are in the same size range that we found for Los Fierros (Coelho et al, 2008;Jácomo et al, 2009;Melo et al, 2007;Rodrigues, 2002), suggesting similar ecological conditions. The largest such study, of 37 resident adult MW studied by Jácomo et al (2009) of our study, two MW co-occupying the same range used areas of 40 km 2 (vHF, perhaps an underestimate) and 52 km 2 : more like the smaller ranges of 20-40 km 2 reported by Dietz (1984) and 40-50 km 2 reported by Trolle et al (2007) and Melo et al (2009). In our study, increases in range sizes after 2005 corresponded to a decline in prey numbers (Emmons, 2009), which suggests an influence of resource density on range size, as we report in more detail in Chapters 4 and 5.…”
Section: Territorialitysupporting
confidence: 44%
“…Maned wolf pairs cooperate to provision young (Bestelmeyer et al, 1996;Melo et al, 2009;Rasmussen and Tilson, 1984). Our brief data sets indicated that in one case the male did not interact at all with the newborn litter or their mother, but when the young were about a month old, he showed repeated, regular return to a focal area near the birth den, consistent with provisioning.…”
Section: Parental Behaviormentioning
confidence: 72%
See 3 more Smart Citations